If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 9y + 5x + 2y = 0 Reorder the terms: 6x + 5x + 9y + 2y = 0 Combine like terms: 6x + 5x = 11x 11x + 9y + 2y = 0 Combine like terms: 9y + 2y = 11y 11x + 11y = 0 Solving 11x + 11y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11y' to each side of the equation. 11x + 11y + -11y = 0 + -11y Combine like terms: 11y + -11y = 0 11x + 0 = 0 + -11y 11x = 0 + -11y Remove the zero: 11x = -11y Divide each side by '11'. x = -1y Simplifying x = -1y
| -2x+3=4x-1 | | 10c^2+8c+12=-9 | | (-3)+17-6(-3)=2 | | (3x/3)=90 | | 5(8x-5)+7=32 | | 4590=40t^4+1560t^2 | | 10c+8c+12=-9 | | .17y+.04(y+8000)=2000 | | 8e^7x=1632 | | (X+15)(x-3)=0 | | -.7=0.2x | | -8x-x^2+63=0 | | 2x+2-1-x-2=2 | | -8x-7=7 | | l-x+6l=7 | | 2x-11=64-3x | | 8x+3x=66 | | 4x+10y+30+(-3)+5x= | | 4-5=-5 | | 3y+4X=85 | | 11(z+3)-4(z-4)=2(z-2)+4(z-3) | | 8-3[3-(3y-7)]= | | Y=1/9x-5 | | 10-X+38=54-17 | | 1629=2x*x | | x+2X+X-4=48 | | 6x+11=-49-8x | | 9-x+37=53-16 | | .125/1=x/16 | | x-x/5=20 | | 12x+5-7=19 | | 3x+14=-14-8x |